2021
DOI: 10.3389/fmicb.2021.629139
|View full text |Cite
|
Sign up to set email alerts
|

ESBL and AmpC β-Lactamase Encoding Genes in E. coli From Pig and Pig Farm Workers in Vietnam and Their Association With Mobile Genetic Elements

Abstract: Animals are considered important sources of ESBL/AmpC-producing bacteria in humans. We analyzed indications of transfer of ESBL/AmpC genes between pigs and pig farmers in Vietnam by analyzing whole genome sequences of 114 ESBL/AmpC-producing E. coli isolated from the two hosts, and performed conjugation experiments and plasmid profiling to confirm that such transfer could have happened. ESBL-encoding genes detected in pigs and pig farmers included blaCTX–M-55, blaCTX-M-27, blaCTX-M-65, blaCTX-M-15, blaCTX-M-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Plasmids are known as an important reason for the rapid spread of bla CTX–M . Recently, CTX-M-55 has been reported to appear on the IncI1, IncF, IncP, and IncA/C plasmids ( Kim J. S. et al, 2017 ; Xia et al, 2017 ; Hounmanou et al, 2021 ). Additionally, the transmission of bla CTX–M is also related to many mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids are known as an important reason for the rapid spread of bla CTX–M . Recently, CTX-M-55 has been reported to appear on the IncI1, IncF, IncP, and IncA/C plasmids ( Kim J. S. et al, 2017 ; Xia et al, 2017 ; Hounmanou et al, 2021 ). Additionally, the transmission of bla CTX–M is also related to many mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%
“…We identified that nearly 50% plasmids also harbored at least one other ARG conferring resistance to critically important antimicrobials. While we do not have access to the farming system, a Vietnamese study has also identified that several ESBL-carrying plasmids also co-carry ARGs conferring resistance to critically important antimicrobials [70]. Additionally, we identified that plasmids from small farms were more likely to co-carry these ARGs than those from medium farms.…”
Section: Discussionmentioning
confidence: 74%
“…These plasmids are known to be highly transmissible among E. coli, further stressing the importance of stopping the spread of plasmids that contain genes conferring resistance to extended-spectrum ß-lactams, fluoroquinolones and colistin [71]. IncF plasmids harboring CTX-M-55 and qnr have also been reported in other regions of Southeast Asia [70].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanisms underlying its increasing ability to cause outbreaks requires an in-depth knowledge of the genetic features of ST405. bla CTX-M-24 has been found in IncP1 ( Hounmanou et al, 2021 ), IncFII ( Yang et al, 2020 ), IncH1B-FIB ( Shen et al, 2019 ), and IncFI plasmids ( Nguyen et al, 2010 ). However, there are no complete sequences of IncI1 plasmids carrying bla CTX-M-24 in publicly available genome databases.…”
Section: Introductionmentioning
confidence: 99%